(untitled) (Medical Forum Monthly, 2024)
Objectives: To find out the prevalence of malaria in district Shaheed Benazirabad (SBA). To Study the proportion of haematological complications among the patients who present with malaria. Study Design: This is descriptive and experimental study. Place and Duration of Study: This study was conducted at Medical Out Patients Department (OPD) and Pathology Department of PUMHSW Peoples Medical College and Hospital at district (SBA) from April 2008 to September 2010. Patients and Methods: A total 1200 cases of malaria diagnosed on basis of clinical and laboratory findings were recorded. The proportion of haemotological complication including anaemia, leucocytosis and thrombocytopenia among these patients were also studied. Results: Out of 1200 patients, 700 (58.33%) were children and remaining 500 (41.77) were adults. Ages of these patients including children and adults ranged between 5 to 65 years with a mean of 35 + 30 years. Male to female ratio in these patients were 1.1:1. The diagnosis of malaria was made by clinical as well as by laboratory findings. The problem of haematological complications as anaemia, leucocytosis and thrombocytopenia were detected among the patient with malaria by determination of Haemoglobin Concentration and Complete Blood Count (CBC). Conclusion: Malaria is more prevalent in district SBA, and many of these patient are children and women. Anaemia, leucocytosis and thrombocytopenia are common haematological complications in them.